Agatha Christie Goes to War - Mills, Rebecca; Bernthal, J. C., 1989- (Milton : Routledge, 2019)
Agatha Christie has never been substantially considered as a war writer, even though war is a constant presence in her writing. This interdisciplinary collection of essays considers the effects of these conflicts on the social and psychological textures of Christie's detective fiction and other writings, demonstrating not only Christie's textual navigation of her contemporary surroundings and politics, but also the value of her voice as a popular fiction writer reflecting popular concerns. Agatha Christie Goes to War introduces the Queen of Crime' as an essential voice in the discussion of war, warfare, and twentieth century literature.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Christie, Agatha, -- 1890-1976 -- Criticism and interpretation; War and literature; LITERARY CRITICISM / Mystery & Detective